The Influence of Study Habits, Learning Creativity, Parental Attention, Learning Facilities, and Peers on the Learning Achievement of Class X Phase E Students in Economics Subjects at SMAN 1 Bukit Sundi, Solok Regency - Yolanda Ifana Putri, Jimmy Ronald, Mona Amelia (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
This study aims to analyze the influence of activity, discipline, family environment, learning facilities, to analyze 1) the influence of learning habits on student learning achievement, 2) the influence of learning creativity on student learning achievement, 3) the influence of parental attention on student learning achievement, 4) the influence of learning facilities on student learning achievement, 5) the influence of peers on student learning achievement, 6) the influence of learning habits, learning creativity, parental attention, learning facilities, and peers simultaneously on the learning achievement of students of class X Phase E in economics at SMA Negeri 1 Bukit Sundi, Solok Regency.This type of research is associative research. The population in this study is class X Phase E students at SMA Negeri 1 Bukit Sundi, Solok Regency.The 2023/2024 school year is 1 sample. Sampling was done using stratified random sampling technique. The instruments used for the research were in the form of a closed questionnaire using the Multiple Linear Regression test and hypothesis test with the t test and the F test.The results of the study show that: First, the variable of learning habits has a positive and significant effect on learning achievement. This is seen from the regression coefficient of 0.131 with tcalculation of 2.854 > t table of 1.982 while the significant value is 0.005>α0.05. Second, the variable of learning creativity has a positive and significant effect on student learning achievement, this is seen from the regression coefficient of 0.139 with t calculation of 2.769 > t table 1.982. while the significant value is 0.007<α0.05. Third, the variable of parental attention has a positive and significant effect on student learning achievement This is seen from the regression coefficient of 0.110 with tcalculated 2.295 > t table 1.982. while the significant value was 0.024>α 0.05. Fourth, the variable of learning facilities has a positive and significant effect on student learning achievement This is seen from the regression coefficient of 0.186 with t calculation of 2,144 > ttable 1,982. While the significant value is 0.034>α 0.05. Fifth, peer variables have a positive and significant effect on student learning achievement This is seen from a regression coefficient of 0.166 with a t-value of 2.742 > ttable 1.982 while a significant value of 0.007>α 0.05. (6) The variables of learning style, confidence, peers, learning discipline and learning facilities together have a positive and significant effect on student learning achievement The value of tcalculation is 43.818 > t table 2.30 and the significant value is 0.001<0.05, This means that H0 is rejected and Ha is accepted.